MRI Features of Intracranial Anaplastic Ependymomas: A Comparison of Supratentorial and Infratentorial Lesions - Kuai, Xin-Ping; Wang, Sheng-Yu; Lu, Yi-Ping; Xiong, Ji; Geng, Dao-Ying; Yin, Bo (Frontiers in Oncology, 2020)
Background: Several previous reports of anaplastic ependymomas have described their imaging features, and most of these studies were case reports. However, no studies have compared the MRI features between the infratentorial and supratentorial anaplastic ependymomas. objective: The goal of this study was to explore magnetic resonance imaging (MRI) characteristics for intracranial anaplastic ependymomas. Material and Methods: We retrospectively reviewed the demographics of 165 patients and MRI findings of 60 patients with supratentorial anaplastic ependymomas (SAEs) and infratentorial anaplastic ependymomas (IAEs) before surgery. The demographics and MRI features for SAEs and IAEs were compared and evaluated. Results: Among the 60 patients, most SAEs (91.7%) were extraventricular, whereas most IAEs (91.7%) were intraventricular. Of sixty intracranial anaplastic ependymomas, most lesions were well defined (n=45) and round-like (n=36). On T1-weighted imaging, compared with the gray matter, the SAEs exhibited heterogeneous signal intensity, whereas IAEs exhibited iso-hypointense signals. T2 signals exhibited greater associations with hyperintense signals in IAEs，however SAEs showed hyperintense or hypointense-hyperintense. On diffusion-weighted imaging (DWI), almost all solid tissues of SAEs appeared as hyperintense, whereas IAEs exhibited iso-hypointense signals. Peritumoral edema and intratumoral hemorrhage occurred more frequently in SAEs. Almost all anaplastic ependymomas exhibited heterogeneous enhancement. Cysts or necrosis were associated with 56 anaplastic ependymomas; however, large cysts were more prevalent in SAEs. On magnetic resonance spectroscopy (MRS), the mean choline/creatine (Cho/Cr) and choline/N-acetyl-aspartate (Cho/ NAA) ratio of anaplastic ependymomas were (6.58±4.26) and (8.84±6.34) respectively, representing typical high-grade tumors. Conclusion: We demonstrate the conventional and functional MRI features of intracranial anaplastic ependymomas, including DWI and MRS. MRI characteristics, such as location, cyst, diffusion restriction and peritumoral edema, differed between supratentorial and infratentorial locations. Cho/Cr and Cho/ NAA ratio of anaplastic ependymomas is increased.